The phenomenon of understanding the conceptual principles of evidence in criminal proceedings regarding corruption offenses in Ukraine - Chyzh, Serhii; Rozumyak, Roman; Kuterha, Maksym; Grokholskyi, Vadym; Salmanov, Oleksii; Dontsov, Denys (DIXI, 2025)
A systematic analysis of judicial practice reveals that gathering evidence in criminal proceedings related to corruption and corruption-related offenses is an exceptionally complex and multidimensional process. This complexity stems primarily from the inherently multifaceted nature of corruption in the modern scientific discourse. Additionally, over the past decade, there has been an ongoing effort to redefine and enhance anti-corruption measures within the state. Key institutions such as the Asset Tracing and Management Agency, the Specialized Anti-Corruption Prosecutor’s Office, and the High Anti-Corruption Court of Ukraine play a pivotal role in addressing corruption-related offenses. The guiding principles for combating corruption in a legally compromised environment are regarded as top priorities, as they form the foundation for investigative and prosecutorial procedures. These principles define the procedural framework, the specific characteristics of investigative and covert operations, and the primary challenges associated with conducting them. Some core conceptual principles include: the extreme complexity of proof in criminal proceedings on corruption and corruption-related criminal offenses in Ukraine; compliance with the requirements of national and international human rights standards; the complex nature of investigative (detective) actions and covert investigative (detective) actions; and interaction with the public.